The Importance of Citizen Scientists in the Move Towards Sustainable Diets and a Sustainable Food System - Oakden, Libby; Bridge, Gemma; Armstrong, Beth; Reynolds, Christian; Wang, Changqiong; Panzone, Luca; Rivera, Ximena Schmidt; Kause, Astrid; Ffoulkes, Charles; Krawczyk, Coleman; Miller, Grant; Serjeant, Stephen (Frontiers in Sustainable Food Systems, 2021)
To enhance sustainability, the food system requires shifts in production, processing and supply. Ideally, a sustainable food system should operate, not only to protect the biosphere, but also to provide nutritious, high-quality food, support social values, an equitable economy, and human and animal health. It should be governed responsibly within a supportive policy environment. Implementing these shifts is a task of immense scale; but citizen participation/engagement has the potential to help make sustainability a reality through distributed learning, dynamic sensing, and knowledge generation. Technological advancements in sensing and data processing have enabled new forms of citizen participation in research. When food system research is embedded within society it can help us to understand which changes toward sustainability work. Indeed, citizen engagement in food systems research has the potential to help bring citizens on-side, supporting the growth of a resilience food culture and sustainable practices (including dietary change). This commentary provides examples of how existing research and alternative food production systems and agroecological practices may provide possible frameworks for citizen participation in food system studies. We highlight potential future food and citizen science approaches. Widening citizen participation and encouraging the involvement of other food system actors, including those in local, national and international governance, is essential to capture the full potential of citizen science in enabling transition to a sustainable food system. For the research community citizen science offers engagement and empowerment of wider communities with science; collecting and analysing data; and creating viable solutions to food system and diet issues.